The Effect of Plyometric Warm-Ups Applied in Different Sets Using Resistance Bands on Jump Performance - Recep TEKİN; Halit HARMANCI; Oğuzhan YÜKSEL (ümit doğan üstün, 2023)
The aim of this study is to investigate the effect of vertical jumping performed in different sets using resistance bands with vertimax device on jump performance as a PAP warm-up stimulus. Fifteen athletes (age: 20.00±2.33; height: 175.07±7.23; weight: 68.71±14.36) from short and middle distances of athletics who have been doing exercise regularly at least 5 days a week for a minimum of 5 years were participated in this study. The athletes participating in this study were firstly warmed up on a treadmill at a speed of 8 km/h for 5 minutes and then 5 minutes of passive rest was applied. After the passive rest period, the athletes were randomly sampled and one of the PAP warm-up protocols consisting of 1, 2 and 3 sets of 10 repetitions with 80 lb resistance on the Vertimax device or without any resistance was applied. The athletes who performed any warm-up protocol were applied. The warm-up protocols that the athletes did not perform were randomly applied in at least 48 hours breaks. Repeated measures of ANOVA test were used to analyze the results of the variables of the athletes participating in the study. The results of the analysis showed that there are significant differences in squat and multi-jump values after warm-up protocols without applying any resistance and 1, 2 and 3 sets of PAP warm-up applications that consisting of 10 repetitions on the Vertimax device (p<0.05). The squat jump height values were found to be significantly higher in 1, 2 and 3 sets of PAP warm-up applications with resistance bands than warm-up protocols without applying any resistance (p<0.05). On the other hand, squat jump height values after 2 and 3 sets of PAP warm-up applications with resistance bands were found to be significantly higher than 1 set of PAP warm-up applications with resistance bands (p<0.05). The multiple jump height values were found to be significantly higher in 2 and 3 sets of PAP warm-up applications with resistance bands than warm-up protocols without applying any resistance (p<0.05). In conclusion, we can say that the vertical jump warm-up applications with resistance bands that includes different sets on the vertimax device as PAP stimulus have a significant effect on jump performance depending on the number of sets.